Saphāp panhā læ nǣothāng kǣkhai sathānakān khwāmmaisangop nai čhangwat chāidǣn Phāk Tai (Saphā Thīprưksā Sœ̄msāng Santisuk Čhangwat Chāidǣn Phāk Tai, 2008)
Social and political conflict in the southern border provinces of Thailand by the Muslim insurgents engaging in guerilla warfare and ways to solve the problem.